Pericapsular Nerve Group Block (PENG Block) and Spinal Anesthesia as Multimodal Analgetic in Patient with Bipolar Hip Arthroplasty: A Case Report - Aidyl Fitrisyah; Stevanus Eliansyah Handrawan; Afrida Yolanda Putri (HM Publisher, 2021)
Introduction. Intertrochanteric fractures are defined as extracapsular fractures of the proximal femur that occur between the greater and lesser trochanter. Bipolar hip arthroplasty is one of the most common major orthopaedic procedures to improve patient’s functional status and quality of life. Spinal anesthesia is a regional anesthetic technique that is performed by injecting local anesthetic drugs into the subarachnoid space to obtain dermatome-level analgesia and skeletal muscle relaxation. Pain after hip replacement originates mainly from the anterior pelvic capsule. The main target for pelvic analgesia is the anterior capsule which is the most richly innervated part of the joint. PENG block is used to block the articular branches to the pelvis. The patient was assessed with an NRS (numeric rating scale) instrument pre and post operative. Case presentation. A-74 year old woman admitted with complaints of pain in the right hip and diagnosed with a closed fracture of the right intertrochanter and planned for bipolar hip arthroplasty with PENG block and spinal anesthesia. Preoperatively the patient was assessed with an NRS (numeric rating scale) instrument with a score of 6. After the procedure, we reevaluated the pain score using NRS was 2 post operative. Conclusion. Patients receiving a PENG block and spinal anesthesia for intraoperative and postoperative analgesia during hip fracture surgery. Prior to spinal anesthesia, PENG block can be performed as a multimodal analgesia in the patient, PENG block expected to facilitate a sitting position during spinal anesthesia and for postoperative pain management